1998
DOI: 10.5006/1.3284887
|View full text |Cite
|
Sign up to set email alerts
|

Role of Carbides in Stress Corrosion Cracking Resistance of Alloy 600 and Controlled-Purity Ni-16% Cr-9% Fe in Primary Water at 360°C

Abstract: Intergranular stress corrosion cracking (IGSCC) of two commercial alloy 600 (UNS N06600) conditions (heat-treated atlow temperature [600LT] and at high temperature [600HT]) and two controlled-purity Ni-16% Cr-9% Fe alloys (carbondoped mill-annealed [CDMA] and carbon-doped thermally treated [CDTT]) were investigated using constant extension rate tensile (CERT) tests in primary water (0.001 M lithium hydroxide [LiOH] + 0.01 M boric acid [H 3 BO 3 ]) with 1 bar (100 kPa) hydrogen overpressure at 360°C and 320°C. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 15 publications
2
23
0
Order By: Relevance
“…So the crack growth in unit time increases with strain rate due to increasing strain applied while that in unit strain decreases with strain rate due to decreasing test time. The work of Was and Lian [9] on Alloy 600 in 360°C primary water confirms this deduction and the results from Boursier et al [23,24] …”
Section: Effect Of Strain Ratesupporting
confidence: 81%
See 2 more Smart Citations
“…So the crack growth in unit time increases with strain rate due to increasing strain applied while that in unit strain decreases with strain rate due to decreasing test time. The work of Was and Lian [9] on Alloy 600 in 360°C primary water confirms this deduction and the results from Boursier et al [23,24] …”
Section: Effect Of Strain Ratesupporting
confidence: 81%
“…Rios et al [30] did U-bend tests in 360°C primary water and found that 1 h sensitization at 700°C increased the initiation time of Alloy 600. Was and Lian [9] reported that the crack length per unit area and maximum crack depth of Alloy 600 after SSRT tests in 360°C primary water decreased with increasing grain boundary carbide coverage and the mitigating effect of grain boundary carbide on SCC was also revealed in Ni-16Cr-9Fe-xC alloys under similar environments [10,11]. Very limited results about the effects of grain boundary carbide density on the SCC initiation of Alloy 690 have been reported due to the difficulty in cracking this material.…”
Section: Effect Of Grain Boundary Carbidesmentioning
confidence: 98%
See 1 more Smart Citation
“…[6]. Was and Lian [27] have examined the roles of carbides in SCC resistance of Alloy 600 and controlled purity Ni-16%Cr-9%Fe in primary water at 633 K. A grain boundary carbide microstructure has been found to be more resistant to IGSCC as compared to an intragranular carbide microstructure and crack growth rate has been found to increase with increasing strain rate [27]. Angeliu et al [28] have investigated repassivation and crack propagation of Alloy 600.…”
Section: Alloy 600mentioning
confidence: 97%
“…Large precipitates are known to act as athermal obstacles together with dislocations contributing to the internal stress. [14] However in this alloy, intragranular carbides do not affect creep [19] or hardening [20] by virtue of their extremely low volume fraction and incoherency. The internal mations: (1) the flow stress is proportional to the strain in Figure 6 and (2) the internal stress is proportional to the flow stress ( int ϭ C flow ).…”
Section: A Applied Stressmentioning
confidence: 99%